2012
DOI: 10.1161/atvbaha.111.241802
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Mitochondrial Oxidative Stress Rescues Coronary Collateral Growth in Zucker Obese Fatty Rats

Abstract: Objective We have previously found abrogated ischemia-induced coronary collateral growth in Zucker obese fatty rats (ZOF) compared to Zucker lean rats (ZLN). Because ZOF have structural abnormalities in their mitochondria suggesting dysfunction, and also show increased production of O2ׄ−, we hypothesized that mitochondrial dysfunction, caused by oxidative stress impairs coronary collateral growth in ZOF. Methods and Results Increased levels of ROS were observed in aortic endothelium and smooth muscle cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 52 publications
1
49
1
Order By: Relevance
“…Previously, in a model of Zucker obese fatty (ZOF) rats with insulin resistance and impaired endothelial function, we found that resolution of mitochondrial oxidative stress restored coronary collateral growth to levels approaching those in control lean rats (47). However, our results did not delineate the precise mechanism(s) by which mitochondrial oxidative stress exerted this negative influence.…”
Section: Mitochondria As Targets Of Oxidative Stresscontrasting
confidence: 80%
See 3 more Smart Citations
“…Previously, in a model of Zucker obese fatty (ZOF) rats with insulin resistance and impaired endothelial function, we found that resolution of mitochondrial oxidative stress restored coronary collateral growth to levels approaching those in control lean rats (47). However, our results did not delineate the precise mechanism(s) by which mitochondrial oxidative stress exerted this negative influence.…”
Section: Mitochondria As Targets Of Oxidative Stresscontrasting
confidence: 80%
“…Also as mitochondrial function is impaired, reactive oxygen species (ROS) production by the mitochondria is increased, which can lead to fragmentation of mitochondrial DNA, further impairing mitochondrial function. dative stress improved respiration profiles and antioxidant defenses (47), which led to partial restoration of coronary collateral growth in the obese rats in response to ischemia. Taken together, these results imply that in obese rats, mitochondrial oxidative stress and the consequential impaired bioenergetic capacity of the mitochondria impairs coronary collateral growth, whereas rectification of the oxidative stress with mitochondrial-directed free radical scavengers restores coronary collateral growth in response to repetitive ischemia (Fig.…”
Section: Coronary Collateral Growth: Roles Of Ucps and Ampk Under Normentioning
confidence: 93%
See 2 more Smart Citations
“…Given that MitoQ is generally adsorbed to the IMM, and the fact that its linker chain enables the penetration of the active antioxidant form, ubiquinol, deep into the membrane core, this molecule is believed to be effective as an antioxidant against mitochondrial lipid peroxidation (144, 294). The reactivity of MitoQ 10 toward O 2 -and other O 2 radicals has been studied in detail (188 (301) sepsis (180,373) diabetes, metabolic diseases, and obesity (38,199,252) ethanol-induced micro-and macrohepatosteatosis (39) neurodegeneration (342) Chronic hepatitis in HCV-infected patients (296) Cationic plastoquinone derivatives…”
Section: B Targeted Mitochondrial Deliverymentioning
confidence: 99%